Towards Agentic Data Engineering: A Contract-Driven System with Self-Evolving Knowledge - Prado, Luan; Azevedo, Leonardo Guerreiro; Veloso, Adriano (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2026.249234, 2026)
Data engineering suffers from long, non-repeatable cycles due to the lack of persistent domain knowledge. This work proposes a contract-driven agentic architecture that externalizes knowledge into executable specifications across sessions. A Data Explorer Agent explores databases while a Data Transformation Agent translates validated contracts into pipelines. Contracts serve as specification, validation, and documentation, forming a feedback loop of recorded, generalized, reusable results. The evaluation of the architecture across diverse databases shows knowledge accumulation and reuse, detection of data quality issues, and the completeness of data pipelines, confirming that knowledge externalization is key to reliable data engineering automation.